Controlled growth of LaFeO3 nanoparticles on reduced graphene oxide for highly efficient photocatalysis. Issue 2 (11th December 2015) - Ren, Xiao; Yang, Haitao; Gen, Sai; Zhou, Jun; Yang, Tianzhong; Zhang, Xiangqun; Cheng, Zhaohua; Sun, Shouheng
Abstract : Using reduced graphene oxide (rGO) as a template and high temperature sol–gel chemistry, we have prepared LaFeO3 nanoparticles (NPs). Abstract : Using reduced graphene oxide (rGO) as a template and high temperature sol–gel chemistry, we have prepared LaFeO3 nanoparticles (NPs). The 15 nm LaFeO3 NPs have a bandgap of 1.86 eV and the LaFeO3 –rGO can function as an efficient catalyst for degradation of methylene blue (MB) or Rhodamine B (RhB) under visible-light irradiation with the electron transfer from the dye to hole dominating the oxidation process. The reported synthesis offers a general approach to perovskite-type NPs for efficient photocatalytic applications.